Depressive symptoms among rural left-behind children and adolescents in China: a large-scale cross-sectional study - Qian-Nan Ruan; Guang-Hui Shen; Su Xu; Dongwu Xu; Wen-Jing Yan (BMC, 2024)
Abstract Background Left-behind children(LBC) in rural China are at increased risk for mental health problems, including depression. This study aimed to estimate the prevalence of depression and identify key associate factors among Chinese rural LBC. Methods A cross-sectional study was conducted using data from 36,612 LBC aged 6 to 18 years old across 596 data collection sites in Nanchong, Sichuan Province, China. Participants completed questionnaires assessing individual factors, family parenting situation, living events, and health-related data. Depression was measured using the Center for Epidemiological Studies-Depression Scale (CES-D). T-tests, chi-square, and logistic regression were performed to identify factors associated with depression. Results The overall prevalence of depression among LBC was 6.75%. Logistic regression analysis revealed that family parenting situations, such as being from blended families (OR = 1.45) or being cared for by other family members (OR = 1.64), and dissatisfaction with the parenting situation (OR = 1.57) were significantly associated with higher odds of depression. Living events, including being misunderstood (OR = 1.82) and having disputes (OR = 1.48), and health-related factors, such as chronic diseases and regular medication use (OR = 2.38), also increased the risk of depression. Conclusions This study highlights the high prevalence of depression among Chinese rural LBC and identifies key associate factors, including family parenting situation, negative living events and health-related factors. Targeted interventions and policies addressing these factors are needed to promote the mental health of this vulnerable population.